Detection of Mechanisms of Social Facilitation - Liaisan V. Khasanova, Flera G. Mukhametzyanova, Ramil R. Khairutdinov, Olga L. Panchenko (Opción, 2019)
In this article within the framework the ontological approach, the mechanism of social facilitation consists in considering the facilitator as an observer, who helps to look at oneself and the situation from the outside and change the subject's from personal to social. As a result, the essence of social facilitation lies in the non-directive management using psychological mechanisms for changing ideas in the presence of an observer in a pre-conflict situation. In conclusion, readiness for the social interaction facilitation is associated with the optimal values of communicative competence, volitional potential and choice of behavior strategy in a conflict situation.